Effect of Cd⁺² on phosphate solubilizing abilities and hydrogen peroxide production of soil-borne micromycetes isolated from Phragmites australis-rhizosphere - Zúñiga-Silva, Jose Roberto (Ecotoxicology (London, England), 2016)
The aims of this work were to evaluate the phosphate-solubilization and hydrogen peroxide (H2O2) production by the soil-borne micromycetes, Aspergillus japonicus, Penicillium italicum and Penicillium dipodomyicola, isolated from Phragmites australis rhizosphere and to study the effect of several concentrations of Cadmium (Cd(2+)) on both variables. Our results showed that P. italicum achieved a higher P-solubilization and H2O2 production than A. japonicus and P. dipodomyicola, as only P. italicum showed a positive correlation (R(2) = 0.71) between P-solubilization and H2O2 production. In dose-response assays, P. italicum was also more tolerant to Cd(2+) (0.31 mM) in comparison to A. japonicus (0.26 mM). Analysis of the 2(4) factorial experimental design showed that P-solubilization by P. italicum was negatively affected by increases in Cd(2+) (p = 0.04) and yeast extract (p = 0.02) in the culture medium. The production of H2O2 was positively affected only by glucose (p = 0.002). Fungal biomass production was reduced significantly (p = 0.0009) by Cd(2+) and increased (p = 0.0003) by high glucose concentration in the culture medium. The tolerance and correlation between P-solubilization and H2O2 production in the presence of Cd(2+) was strain and species dependent. The effects of Cd(2+), glucose, ammonium sulfate and yeast extract on those variables were evaluated through a two-level factorial design. P. italicum is promising for P-solubilization in soils contaminated with Cd(2+) and may be an alternative for manufacture of biofertilizers to replace chemical fertilizers